2018
DOI: 10.5812/jhealthscope.61412
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hospital Waste: A Case Study in Tehran, Iran

Abstract: Background: There has been a major focus on hospital waste management and challenges of infectious waste removal in different researches. The aim of this study was to analyze medical wastes and examine the current situation of hospital waste management in Tehran, Iran. Methods: Five hospitals were selected, and a questionnaire was developed, based on the World Health Organization (WHO) guidelines for the assessment of hospital waste management. Moreover, hospital waste managers, hospital authorities, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…GARCÍA-UBAQUE; ZAFRA-MEJÍA, TRAN et al, 2019;FARROKHI et al, 2016;ANOZIE, 2017;AHMAD et al, 2019;URIOSTE et al, 2018;MARCZAK, 2016;AUGUSTIN et al, 2016;FARZADKIA et al, 2018;JOVANOVIĆ et al, 2016;GAO et al, 2018;KRISHNAN;DEVAMANI;JAYALAKSHMI, 2015;OLIVEIRA;VIANA;CASTAÑON, 2018;PRAYITNO et al, 2018;THANH et al, 2016;SREEREMYA;RAJIV, 2017;NOGUEIRA et al, 2018;KUCHIBANDA;MAYO, 2015;YOUSEFI;AVAK ROSTAMI, 2017;NEVEU C;MATUS C, 2007;AL-MOMANI et al, 2019;PACHAURI et al, 2019;AFOLABI et al, 2018;DEWI et al, 2019;NJUANGANG;LIYANAGE;AKINTOYE, 2018;KIM et al, 2018;MUKHAIBER, 2017;JASEM;JUMAHA;GHAWI, 2018;GARIBALDI et al, 2017;NAMBURAR et al, 2018).…”
Section: Resultados E Discussõesmentioning
confidence: 99%
“…GARCÍA-UBAQUE; ZAFRA-MEJÍA, TRAN et al, 2019;FARROKHI et al, 2016;ANOZIE, 2017;AHMAD et al, 2019;URIOSTE et al, 2018;MARCZAK, 2016;AUGUSTIN et al, 2016;FARZADKIA et al, 2018;JOVANOVIĆ et al, 2016;GAO et al, 2018;KRISHNAN;DEVAMANI;JAYALAKSHMI, 2015;OLIVEIRA;VIANA;CASTAÑON, 2018;PRAYITNO et al, 2018;THANH et al, 2016;SREEREMYA;RAJIV, 2017;NOGUEIRA et al, 2018;KUCHIBANDA;MAYO, 2015;YOUSEFI;AVAK ROSTAMI, 2017;NEVEU C;MATUS C, 2007;AL-MOMANI et al, 2019;PACHAURI et al, 2019;AFOLABI et al, 2018;DEWI et al, 2019;NJUANGANG;LIYANAGE;AKINTOYE, 2018;KIM et al, 2018;MUKHAIBER, 2017;JASEM;JUMAHA;GHAWI, 2018;GARIBALDI et al, 2017;NAMBURAR et al, 2018).…”
Section: Resultados E Discussõesmentioning
confidence: 99%
“…In most hospitals, the waste was properly segregated and disinfected and only a few hospitals (20%) had HSW storage [63] Patiala city, Punjab, India There was an absence of proper waste management and a general lack of awareness of the hazards of HSW [55] Rajshahi City, Bangladesh The unsafe practice of open dumping was still practiced and clinical waste was not separated from non-hospital waste [56] Pokhara, Nepal Hazardous wastes in the HSW were above WHO limits and awareness of safe disposal techniques was low [57] Jogyakarta, Indonesia The waste was properly handled but recycling has not been considered [64] Mazandaran province, Iran 36.1% of the HSW generated was hazardous and over half the hospitals considered disposal of their waste by incineration [65] Anambra, Nigeria…”
Section: Tehran Iranmentioning
confidence: 99%
“…[5][6][7] Inappropriate waste management in hospitals may lead to the risk of needle-stick injuries, the transmission of infectious diseases, [8][9][10][11] as well as infect hospital staff, patients, and the general public. 7,12,13 Furthermore, additional risks occur during the handling and sorting of health-care waste from hospital facilities and from scavenging at disposal place. 9 In 2015, the World Health Organization (WHO) reported that injections with contaminated syringes and needles were responsible for as many as 1.7 million hepatitis B infections, 315 000 hepatitis C infections and 33 800 new HIV infections.…”
mentioning
confidence: 99%
“…7 In Iran, although, the practical regulation and disposal policy have been established in recent years, inappropriate medical waste management still appears to be a serious problem faced in hospital facilities. 6,12 Notable, it was evidence that low awareness of hospital staff about the health hazards of medical waste 11,15,16 and their poor intention and responsibility concerning the implementation of waste management regulations are the most common barriers linked to inappropriate medical waste management in Iran like as for other developing countries. 12,17 Thus, there is a need for intervention training programs and continues to practice for all staff involved in medical waste recycling.…”
mentioning
confidence: 99%
See 1 more Smart Citation